Temperature Effect on Erythrocyte Membrane Permeability for Cryoprotectants with Different Hydrophobicities - Davydova, E. V.; Gordienko, O. I. (Problems of Cryobiology and Cryomedicine, 2009)
There were measured the permeability coefficients for native and pCMBS-treated human erythrocytes for 1,2-propane diol (1,2-PD) and dimethyl sulfoxide (DMSO) within 3–37°C temperature range and the values of activation energy for these cryoprotectants’ penetration within certain temperature ranges were determined. Erythrocyte cooling below physiological temperatures was shown to result in thermotropic changes of membrane state. The most pronounced changes in activation energy were observed within 27–30 and 12°C range. Sharp decrease in activation energy of penetration of 1,2-PD hydrophilic cryoprotectant within 30–37°C range disappears after erythrocyte treatment with pCMBS, testifying to a significant contribution of 1,2-PD protein hydrophilic channels into a transmembrane flow. The presence of kinks in Arrhenius plots and an increase in activation energy of penetration of both hydrophilic 1,2-PD and hydrophobic DMSO within temperature range below 12°C is not eliminated via erythrocyte treatment with sulphhydryl reagent. Thus, these effects can not be explained by closing the protein pathways of permeability for studied substances and they are